Effects of Dopamine Medication on Sequence Learning with Stochastic Feedback in Parkinson's Disease - Seo, Moonsang; Beigi, Mazda; Jahanshahi, Marjan; Averbeck, Bruno B. (Frontiers in Systems Neuroscience, 2010)
A growing body of evidence suggests that the midbrain dopamine system plays a key role in reinforcement learning and disruption of the midbrain dopamine system in Parkinson's disease (PD) may lead to deficits on tasks that require learning from feedback. We examined how changes in dopamine levels (‘ON’ and ‘OFF’ their dopamine medication) affect sequence learning from stochastic positive and negative feedback using Bayesian reinforcement learning models. We found deficits in sequence learning in patients with PD when they were ‘ON’ and ‘OFF’ medication relative to healthy controls, but smaller differences between patients ‘OFF’ and ‘ON’. The deficits were mainly due to decreased learning from positive feedback, although across all participant groups learning was more strongly associated with positive than negative feedback in our task. The learning in our task is likely mediated by the relatively depleted dorsal striatum and not the relatively intact ventral striatum. Therefore, the changes we see in our task may be due to a strong loss of phasic dopamine signals in the dorsal striatum in PD.